Micromobility as a catalyst for sustainable urban transportation: A backcasting approach on decarbonisation and energy consumption - Shahnaz Nabila Fuady; Paul Christian Pfaffenbichler; Georgia Charalampidou; Yusak Octavius Susilo (Sustainable Futures)
This study explores micromobility's role in advancing Vienna's sustainability goals through backcasting. It examines how increasing urbanization and private vehicle use contribute to rising energy consumption and CO2 emissions. The study highlights micromobility, including lightweight vehicles, as a key solution for reducing car trips and achieving sustainable transport. Challenges, such as slow electric vehicle adoption and the need for decarbonization, complicate this transition. The findings emphasize the importance of adaptable policies to fully leverage micromobility's potential for a greener Vienna by 2040, offering valuable insights for global urban planners and policymakers.